2011
DOI: 10.1002/esp.2242
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of runoff and soil loss from two differently sized plots in a subtropical environment (Brazil)

Abstract: Studies of soil erosion on small plots present upscaling problems. The results in the literature on the effect of slope length (i.e. scale) on runoff and soil erosion are contradictory. Furthermore, most studies that examine scale effects measured through erosion plots have been conducted in Mediterranean environments. The objective of this study was to assess the effects of plot size on runoff and soil loss in a subtropical environment. Other measurements were taken to appraise the topsoil property changes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 48 publications
1
15
0
2
Order By: Relevance
“…In Brazil, Thomaz and Vestena (2012) found that increasing plot size reduces runoff results because the surface is more complex, while soil erosion values are comparable; they note that 100 m 2 erosion plots are acceptable as a representative area (Hudson, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil, Thomaz and Vestena (2012) found that increasing plot size reduces runoff results because the surface is more complex, while soil erosion values are comparable; they note that 100 m 2 erosion plots are acceptable as a representative area (Hudson, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…In most run-on experiments, no explanations were given for the use of certain flow rates. In a previous study by Thomaz & Vestena (2012), the authors showed that during one year, even after high-intensity and long-duration rainfalls, no rill was formed in the Oxisol. Therefore, a reasonable amount of extra flow was used to produce the effect of rill development.…”
Section: The Experiments Was Conducted In Guarapuava Inmentioning
confidence: 91%
“…To make the rainfall simulation more realistic, a total of 71 natural rains in a typical year (1920 mm) in the subtropical region of Guarapuava were analyzed for volume (mm), intensity (mm h), and duration (h or min) (Thomaz & Vestena, 2012).…”
Section: The Experiments Was Conducted In Guarapuava Inmentioning
confidence: 99%
See 1 more Smart Citation
“…Os processos erosivos atuam como principais agentes no transporte e deposição superfi cial do carbono orgânico na paisagem (Starr et al, 2006;Ritchie et al, 2007;Schwanghart & Jarmer, 2011), promovendo ainda a remoção seletiva dos agregados do solo (Thomaz & Vestena, 2012). Considerando a desagregação primária de partículas mais fi nas (diâmetros reduzidos) e mais leves (de menor densidade) (Lal, 1995), os sedimentos são usualmente enriquecidos não apenas com as partículas de silte e argila transportadas em conjunto com as formas estáveis de carbono orgânico presentes no solo (Baldock & Skjemstad, 2000), mas também de matéria orgânica particulada de fácil decomposição (Chaplot et al, 2005).…”
Section: Ciclo Global Do Carbonounclassified